The effectiveness of internship practice for English language majors - Dung, Doan Thi Hue; Tung, Nguyen Nhu; Thoi, Pham Khac (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2020)
This article examines the internship practice of English-majored students at Hong Bang International University during the academic years 2019 - 2020 and explores the effectiveness of internships, based on the perspectives of all stakeholders: the employers, the lecturers, and the interns. The article employs both qualitative and quantitative data from the survey questionnaires and interviews with 83 students, 67 employers, and 7 lecturers. The findings show that internship provides the interns a practical environment to develop essential skills and competencies ready for their future work. Based on the findings of the study, the authors make suggestions on the course design and the training of essential skills and competencies for English majored students with Commerce - Media specialization, in particular.